Nutritional assessment, body composition, and low energy availability in sport climbing athletes of different genders and categories: A cross-sectional study - Mora-Fernandez, A.; Argüello-Arbe, A.; Tojeiro-Iglesias, A.; Latorre, J. A.; Conde-Pipó, J.; Mariscal-Arcas, M. (Nutrients, 2024)
Climbing is an Olympic discipline in full development and multidisciplinary in nature, where the influences of body composition and nutritional status on performance have not yet been clarified despite the quest for a low weight in anti-gravity disciplines such as climbing. The present cross-sectional study aimed to conduct nutritional (3-day dietary diaries) and body composition (ISAK profile) assessments on sport climbing athletes by gender and climbing level during the months of February and March 2024. The t-test for independent samples and the Mann-Whitney U-test, as well as an ANOVA and the Kruskal-Wallis H-test, were used to compare the distributions of two or more groups, respectively, and Pearson`s and Spearman`s correlation coefficients were used to estimate the correlations between the different variables. The mean age of the 46 Spanish climbers (22 men and 24 women) was 30 years (SD: 9) with 7.66 years of experience (SD: 6.63). The mean somatotype of the athletes was classified as balanced mesomorph. Negative correlations were observed between fat mass variables and climbing level (p < 0.010), and positive correlations were observed with forearm circumference (p < 0.050). The mean energy availability (EA) was 33.01 kcal-kg FFM-1d-1 (SD: 9.02), with 55.6% of athletes having a suboptimal EA status and 35.6% having low energy availability (LEA). The carbohydrate and protein intakes were below the recommendations in 57.8% and 31.1% of athletes, respectively. There were deficient intakes of all micronutrients except phosphorus in males. These findings suggest that climbing athletes are at a high risk of developing low energy availability states and concomitant problems. Optimal nutritional monitoring may be advisable in this type of athlete to try to reduce the risk of LEA.